SEASONAL VARIATIONS ON SEMEN CHARACTERISTICS OF FATTAILED AND GARUT RAMS UNDER TROPICAL CONDITIONS - Isnaini, Nurul; Wahjuningsih, Sri; Falah, Moh. Miftahul; Fajarrofa, Alfa; Harsi, Tri; Sukmawati, Eros (Jurnal Kedokteran Hewan, 2021)
This study investigated the influences of rainy and dry seasons on semen characteristics of fat-tailed and Garut rams under tropical conditions. A total of 4 healthy rams (2 fat-tailed rams and 2 Garut rams) aged 3 to 4 years old were used in this study. The semen was collected from each ram during November 2016 to February 2017 (rainy season) and May to August 2017 (dry season). The measurement of semen characteristics including semen volume (SV), sperm concentration (SpC), total sperm (TSp), individual sperm motility (ISM), post-thawing sperm motility (PTSM), and frozen semen production (FSP). The rainy season resulted higher SV (P= 0.021), TSp (P= 0.005), ISM (P= 0.028), and FSP (P= 0.005) than the dry season. On the other hand, fat-tailed rams had higher (P0.001) SV, TSp, and FSP compared to Garut rams. There was no interaction (P0.05) between season and breed on all semen characteristic parameters found in the present study. It can be concluded that the semen collection during the rainy season had a beneficial impact to produce high-quality semen for artificial insemination program than in the dry season. Fat-tailed rams have better semen characteristics compared to Garut rams.